Makna Sampul Majalah Tempo tentang Pemilihan Umum edisi Januari 2024 - Syafitri, Dwi Imas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tempo magazine covers use strong visuals and striking illustrations to highlight the main topics of each issue. This research analyzes the visual meaning of three covers of the January 2024 edition of Tempo magazine—